If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3m + -4)(2m + 5) = 0 Reorder the terms: (-4 + 3m)(2m + 5) = 0 Reorder the terms: (-4 + 3m)(5 + 2m) = 0 Multiply (-4 + 3m) * (5 + 2m) (-4(5 + 2m) + 3m * (5 + 2m)) = 0 ((5 * -4 + 2m * -4) + 3m * (5 + 2m)) = 0 ((-20 + -8m) + 3m * (5 + 2m)) = 0 (-20 + -8m + (5 * 3m + 2m * 3m)) = 0 (-20 + -8m + (15m + 6m2)) = 0 Combine like terms: -8m + 15m = 7m (-20 + 7m + 6m2) = 0 Solving -20 + 7m + 6m2 = 0 Solving for variable 'm'. Factor a trinomial. (-5 + -2m)(4 + -3m) = 0Subproblem 1
Set the factor '(-5 + -2m)' equal to zero and attempt to solve: Simplifying -5 + -2m = 0 Solving -5 + -2m = 0 Move all terms containing m to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -2m = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -2m = 0 + 5 -2m = 0 + 5 Combine like terms: 0 + 5 = 5 -2m = 5 Divide each side by '-2'. m = -2.5 Simplifying m = -2.5Subproblem 2
Set the factor '(4 + -3m)' equal to zero and attempt to solve: Simplifying 4 + -3m = 0 Solving 4 + -3m = 0 Move all terms containing m to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3m = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3m = 0 + -4 -3m = 0 + -4 Combine like terms: 0 + -4 = -4 -3m = -4 Divide each side by '-3'. m = 1.333333333 Simplifying m = 1.333333333Solution
m = {-2.5, 1.333333333}
| 4+ln(x+3)=3 | | 8z-0.6=9z | | 5y-6=6y-1 | | -5j+(-2)+3= | | y--9=3/4(x-5) | | 2z+6=4z-3 | | =2u^10v^9w^8*w*9v^2*4u^9 | | (2m^2*n^-2*p^0/m^-2)^3= | | x^2*x^9= | | 0.3(0.2x-1)=0.4(0.5x-1) | | 2/5-7/20x=2 | | 3x-2=1/2=x/3 | | 5h+2(1-h)=-5 | | -4.3-k=-4.57 | | 16-6r=25-3r | | 4x-0.6-1.6x+2.9x+4= | | 6x+8=8x-3 | | -17.2=x-7.7 | | 6x+24+2x=68 | | n-6=n-8 | | 4-y/-17 | | 9+(-16)=-1 | | V/4=3/4 | | 2=b/8 | | 13x+88=107 | | f(x)=5x^2-19x-4 | | 6x-4=10+x | | 6x^2y^3/12x^3y | | x+5=-25 | | B+42=100 | | 8x^2-(-2-1)x+32=0 | | 8x^2-(2-1)x+32=0 |